Retail Banking: Indian Scenario - Jaiswal, K. S.; Singh, Neetu (Indian Journal of Marketing, 2007)
Retail Banking is a typical mass-market banking where individual customers use local branches of a larger commercial bank. It refers to the dealing of commercial banks with individual customers. Services offered include fixed, current/savings accounts mortgages, loans (eg. personal, housing, auto and educational) debit cards, credit cards and so forth.